Improvement of sexual behavior and semen quality by therapeutic approach and zinc supplementation on Karan Fries - SABHAPATI, M; RAINA, V S; BHAKAT, M; MOHANTY, T K; SHIVAHRE, P R; MONDAL, G; GUPTA, A K (The Indian Journal of Animal Sciences, 2016)
Sub-fertility is one of the major concerns in crossbred bulls as 42.98% bulls are getting culled due to sub- fertility problems therefore, a study was planned on 18 Karan Fries bulls producing poor quality semen or not mounted. They were randomly grouped into 3 treatment groups of 6 animals each and 2 normal bulls were kept as control. Sexual behavior and semen quality were studied during pre-therapy (1 month), therapy (90 days) and post- therapy (90 days) period. Data were analyzed using ANOVA. During therapy period, first group treated with 10 g of herbal product orally, second group with 0.0082 mg of GnRH intramuscularly at 10 days interval and third group with 80 ppm of zinc for 90 days for each group. The results depicted that herbal and GnRH treatment significantly reduced the reaction time, whereas herbal, GnRH treatment and zinc supplementation significantly improved the libido score and reduced per cent of non-mounts during the therapy and post-therapy period. The volume of semen and level of testosterone improved in all treatments groups. Herbal, GnRH treatment and zinc supplementation increased the average number of good and medium quality ejaculates/month/bull and maximum efficiency achieved during the treatment period. There was increase in percent live sperm and decrease in abnormality in herbal treated and zinc supplemented group. Therefore, it can be concluded that GnRH therapy, herbal treatment and zinc supplementation will be effective to overcome the sub-fertility problem in crossbred bulls.